2020
DOI: 10.38136/jgon.775326
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation in Assisted Reproduction and Fertility Preservation

Abstract: Cryopreservation is the technique of keeping living cells or tissues at ultralow temperature that no metabolic or biochemical activity can ocur. The use of cryopreservation techniques is highly attractive and has been increasingly applied worldwide. Cryopreservation of sperm, oocytes and embryos have been central to improvements in the assisted reproduction treatment success with many potential applications. Embryo cryopreservation is an established procedure and has been increasingly used due to novel indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to the United States Department of Health and Human Services report, smoking during pregnancy increases the risk of stillbirths, and the babies of pregnant women who smoke are born more prematurely and at lower birth weights than the babies of nonsmoker pregnant women (11). Nationwide studies on smoking rates in Turkey have reported smoking rates in pregnant women between 7.3% and 16% (12).…”
Section: Introductionmentioning
confidence: 99%
“…According to the United States Department of Health and Human Services report, smoking during pregnancy increases the risk of stillbirths, and the babies of pregnant women who smoke are born more prematurely and at lower birth weights than the babies of nonsmoker pregnant women (11). Nationwide studies on smoking rates in Turkey have reported smoking rates in pregnant women between 7.3% and 16% (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metabolites of harmful substances in tobacco smoke are higher in individuals who are passively exposed to tobacco smoke than in those who have never been exposed to tobacco smoke. In this way, pregnant women and children are the ones who are passively exposed to tobacco smoke more (10,11). Pregnant women' smoking is a more serious health problem because of the harm it causes to the foetus.…”
Section: Introductionmentioning
confidence: 99%